HISTORIOGRAPHY AND SOURCES TO STUDY ETHNOGRAPHIC RESEARCHES OF GUTSULSCHINA AT THE END OF XIX – THE BEGINNING OF XXI CENTURY - Дмитрук, І. Ф. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
This article is the effort to study the ethnographic researchers about Hutsulshchyna in the 20th century and to make the universal review of sources and historiography. The special attention is given to study the main stage in process of ethnographic researchers of Hutsulshchyna and their character.